Aplikasi Belajar Bahasa Daerah Pulau Taliabu Berbasis Android - La Dame, Julham; Saya, Safril; Rosmiati, Rosmiati (Department of Electrical Engineering, University of Patria Artha, 2021)
The progress of the times has brought various changes in various fields of human life, one of which is the use of regional languages. Taliabu Island is one of the areas within the province of North Maluku, which has its native language or Taliabu language. Currently the use of the Taliabu language has been forgotten by the people of the area, this is built by technological advances that continue to develop, making people forget the importance of culture which should be preserved as the identity of the area. This study aims to build a local language learning application for the island of Taliabu using android as a platform to make it easier for people there or to take the initiative to learn Taliabu. Selection of android as the operating system, because android is currently widely used, ranging from adults to even children, this will have a positive impact to help local governments who are trying to preserve regional culture, one of which is the Taliabu area. Applications will be built using the RAD (Rapid Application Development) method as a system development method, which consists of several stages of work, namely the analysis, design, coding and testing stages. The application of the dictionary for the local language of Taliabu Island based on Android can be translated into Indonesian - Taliabu and Indonesian - Maluku. The resulting output is the form of the translated text and the vocabulary that you want to know the meaning.